2018
DOI: 10.1186/s40862-018-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on learning trajectories of non-native Chinese instructors as successful Chinese language learners

Abstract: This paper reports a qualitative study on the Chinese language learning trajectories of non-native Chinese instructors as successful Chinese language learners. While some literature has been found on studying good learners of English and other languages, there is a lack of research on studying good learners of the Chinese language, especially on their life-long Chinese learning process. Six active instructors teaching Chinese at K-12 schools or universities in the United States, whose native language is Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
3
4
0
Order By: Relevance
“…The findings revealed that good students will use various learning strategies to self-regulate their learning (Liu & Wang, 2018). The research also supported by previous studies of Wu (2007); Lew (2020); Yee et al (2021) revealing that good Malay students learnt Mandarin through the practice and application of Mandarin, which belongs to two learning strategies namely cognitive strategies and social strategies.…”
Section: 03 Often Mean=m Standard Deviation=sdsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings revealed that good students will use various learning strategies to self-regulate their learning (Liu & Wang, 2018). The research also supported by previous studies of Wu (2007); Lew (2020); Yee et al (2021) revealing that good Malay students learnt Mandarin through the practice and application of Mandarin, which belongs to two learning strategies namely cognitive strategies and social strategies.…”
Section: 03 Often Mean=m Standard Deviation=sdsupporting
confidence: 85%
“…Some researchers have referred to and adopted Oxford's learning strategies on how leaners can improve their language proficiency and achievement in the Mandarin language as a second or foreign language via language learning strategies approaches. Liu and Wang (2018) demonstrated that good students in learning Mandarin were actively involved in the language learning process and found ways to overcome linguistic, affective, or environmental obstacles. Besides, they also use various strategies to self-regulate their learning throughout their learning careers.…”
Section: Introductionmentioning
confidence: 99%
“…It is easier to learn by mapping the lyrics of the songs to be performed in the Chinese Pinyin and Italian tables, and this method has been verified by the success of the recital. The results also show that Bel canto singing techniques on performing Chinese art songs using language as a cut-in has achieved good results, which is confirmed (Lei, 2015;Li, 2016;Liu & Wang, 2018;Chen, 2019;Olabimtan, 2020;Kang & Hovy, 2021). Simultaneously, it is easier for non-native Chinesespeaking singers to use English as examples.…”
Section: Discussionsupporting
confidence: 53%
“…Learners' reaction time and d-prime results became more native-like after two months of classroom study but plateaued thereafter. Besides that, Liu and Wang (2019) included that the six participants all had experiences studying in China, and all held lifelong learning attitudes as well as demonstrated various selfregulation strategies with strong self-motivation and dedication. While they all took Chinese classes at college, only two of them studied prior to college, which is encouraging for Chinese learners who were unable to learn Chinese from an early age.…”
Section: Attitudementioning
confidence: 99%